Mantra yoga as a probable measure in improving sleep and reaction time among commercial drivers: An exploratory pilot study - Neha Raghuwanshi; Jyoti Keswani; Hemanshu Sharma; Gulab Rai Tewani; Pradeep M.K. Nair (Elsevier, 2022)
Problem considered: Road accidents are a growing concern in developing countries that needs immediate attention. The present study evaluated the role of Maha Mrityunjaya mantra (MMM), a vedic practice in reducing reaction time, burnout and improving sleep among commercial drivers. Methods: Fifty commercial drivers (Age 39.92 ± 8.64) were enrolled for a 2 months MMM chanting session (21 rounds, 15 min daily, 5 sessions/week). The effects were measured at the baseline and at the end of 2 months using ruler drop test (RDT), Pittsburgh Sleep Quality Index (PSQI) and Oldenburg burnout inventory (OLBI). Results: The average work experience and duration of working hours per day were 15.1 ± 7.75 years and for 8.7 ± 1.7 h respectively. We observed significant changes in PSQI scores (Pre- 7.44 ± 3.9, Post- 4.82 ± 2.32; p < 0.01), OLBQI (Pre-38.24 ± 3.22, Post-34.24 ± 2.64; p < 0.01, effect size 1.000) and RDT scores (Pre-16 ± 3.9, Post-10.28 ± 2.79; p < 0.01). Spearman's correlation revealed a weak positive association between improvement in sleep with reaction time (rs = 0.247) and burnout scores (rs = 0.097). Conclusion: The present study concludes MMM chanting may be beneficial in improving the reaction time among drivers, which may be useful as a strategy in preventing road traffic accidents. However, robust randomized control trials are warranted before making generalized recommendations.